OPTIMALISASI PEMBERDAYAAN WILAYAH PERTAHANAN DALAM MENDUKUNG MANAJEMEN PERTAHANAN (STUDI DI KODIM 1408/BS KODAM VII/WIRABUANA) - , AGUNG ZAMANI, Prof. Dr. HA. Sudibyakto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose was developed to empower the defense in support of defense management in Makassar 1408/BS Kodim are as follows: (1) to assess the condition of the empowerment of the defense, (2) analyze the factors obstacle in the empowerment zone defense, and (3) starategi formulate optimization empowerment zone defense. The research method used was survey method through a qualitative approach, interviews with a purposive sampling method, observation, and research in the field has continued to study literature in organizational management, personnel capabilities, and infrastructure in regional command Kodim 1408/BS Makassar, in order to obtain a accurate data to be analyzed, then the outcomes could be used as an input to empower the defense at the regional command. The results showed that : First, conditions of the empowerment zone defense in order to support the management of defense in the Kodim 1408/BS been going according to plan well with the aspect of geography, demography, and social conditions of the people of Makassar, but not optimal because of the limitations of operational software that can be guided in the field and low participation of any empowerment zone. Second, the factors that led to the empowerment of the defense has not been optimum consists of internal factors such as limitations in organizational management, personnel capabilities, and infrastructure, as well as external factors such factors as the command of the military command, the specific conditions of the people of Makassar, and limited support from elements communities around the Kodim 1408/BS. Third, strategies are developed to optimize the empowerment zone defense in favor of the defense management in the Kodim 1408/BS is to enhance the professionalism of personnel, to defend the country to raise awareness, promote the implementation of territorial development in proportion, realizing empowerment zone defense in favor of the defense management, empowerment and realizing regional command.